Lineament Density and Implications for the Distribution of Ground Fissures After 2021 MW 7.3 Flores Sea Earthquake on Kalaotoa Island, Indonesia - Baso Rezki Maulana; Muhammad Sulhuzair Burhanuddin; Muh. Fikri Akbar (UIR PRESS, 2023)
A 7.3 MW earthquake occurred at 11:20 am on December 14, 2021, in the Flores Sea, and the main shake was centered ±100 km north of Maumere, Indonesia, with a depth of 14.3 km, antecedent a landslide. This research consists of two stages, namely: quantitative data collection in the form of tectonic lineament density measurements using Shuttle Radar Topography Mission (SRTM) data which is extracted manually using GIS-based applications, and qualitative data in the form of field observations which include strike-dip measurements of rocks, lithological data, morphological conditions, ground fissures, and the distribution of damage caused after 2021 earthquake. This study focused on analyzing the value of lineament density, its correlation to the history of seismicity and surface lithological conditions, and the impact after the 2021 earthquake damage. The lineaments of the southern area are dominated by NE – SW orientation along with various lithological conditions and with lineament density values very low – very high. A crack width from 0.5 to 112 cm, and a vertical offset occurs with a depth of up to 270 cm. The western area is dominated by lineament with an orientation NE – SW with a crack width from 8 to 18 cm, and there is a vertical offset with a depth of up to 24 cm. The distribution of ground fissures in the Garaupa Raya area is categorized as low. The orientation of the northern area lineament is relatively NW – SE directional and the lineament density value is categorized as low. Horizontal displacement with an orientation of NW – SE is found at the port of Kalaotoa Island, Kawawo village with measured crack width of ±17 cm, an observable horizontal offset from 15 to 24 cm, and a vertical offset of ±12 cm with a trend of movement towards the south.